Factors associated with self-reported suboptimal antiretroviral adherence and limited retention in care among people living with HIV who attend a large ART clinic in Panama City, Panama. - Amanda Gabster; Félix Díaz Fernández; Juan Miguel Pascale; Angelique Orillac; Samuel Moreno-Wynter; Casey D Xavier Hall; Eugenia Flores Millender; Frank Frankie Wong; Mónica Jhangimal; Anyi Yu-Pon; Cristel Rodríguez-Vargas; Diógenes Arjona-Miranda; et al. (PLoS ONE)
Background The prevalence of HIV in Panama is estimated to be 1.0%; only 71% of individuals on antiretroviral treatment (ART) were virally suppressed in 2022. This study aimed to describe the prevalence of suboptimal adherence (≥1 missed doses in previous four weeks) and limited retention in HIV care (≥1 missed HIV care appointments in previous 12 months) among adults (aged ≥18 years) who attended the most populous urban ART Clinic in Panama City. Methods In this cross-sectional study, participants completed a self-administered questionnaire. Univariable and bivariable analyses were used to describe the prevalence of suboptimal adherence and limited retention in HIV care. Multivariable logistic regression identified factors associated with suboptimal adherence at p<0.05. Results We included 375 participants (209 identified as men, 158 as women, 8 another gender). Of those who responded, 37.3% (n = 125/335) reported suboptimal adherence: 28.6% (n = 53/185) of men, 49.0% (n = 71/145) women, 20.0% (n = 1/5) another gender; p<0.01; 18.6% (n = 69/371) reported limited retention in care:13.6% (n = 28/206) men, 24.2% (n = 38/157) women, 37.5% (n = 3/8) another gender, p = 0.01. In multivariable analyses, suboptimal adherence was associated with gender (49.0%women vs. 28.6% men, AOR = 1.86, 95%CI:0.97-3.57), depressive symptoms:46.2% severe symptoms vs. 28.1% minimal-mild, AOR = 2.19,95%CI:0.96-5.04), and lifetime intimate partner emotional violence (IPV) 48.2% vs.no emotional IPV 32.2%, OR = 1.96,95%CI:1.15-2.90, and lifetime physical IPV 46.9% vs.no physical IPV 32.6%, OR = 1.82, 95%CI:1.15-2.90. In unadjusted analyses, limited retention in care was associated with gender (24.2%women vs.13.6% men OR = 2.03, 95%CI:1.18-3.49), difficulty paying rent/mortgage/utilities (22.6% vs.14.9% no difficulty paying, OR = 1.67,95%CI = 0.98-2.83); no variables were associated in the multivariable model. Conclusions This study found high prevalence of suboptimal ART adherence and limited retention in care, especially among women; these factors were associated with severe depressive symptoms, as well as lifetime emotional and physical IPV. These results show the need for integrated mental health and IPV intervention for all individuals, including focused support for women.